Microbial fermentation biotechnology of cooked chicken bone novel substrate for L-asparaginase production - Makky, Essam A.; Ali, Muna Jalal (University of Kerbala, 2019)
L-asparaginase is an efficient anti-cancer enzyme due to its remarkable property in hydrolyzing essential amino acid of acute lymphoblastic leukemia cancer (L-asparagine) into aspartic acid and ammonia. Various sources of L-asparaginase had been identified including extraction from animal or plant as well as through microbial fermentation. Generally, researchers preferred to generate L-asparaginase by engaging microbe as the L-asparaginase producer because the abundant amount of L-asparaginase can be harvested in an affordable manner. The present study aimed at screening, optimization, and purification of microbial production L-asparaginase in presence of cooked chicken bone wastes as substrate. Different controlling parameters were studied including physiological (incubation period and temperature, initial pH-value, and substrate concentration), nutritional (carbon and nitrogen sources) and microbial parameters (inoculum sizes). As a result, the highest amount of L-asparaginase was harvested when the fermentation was incubated at 40 °C for 2 days at pH 9 in presence of 1% w/v of cooked chicken bone waste as a sole substrate. Besides that, starch and ammonium chloride were discovered as the best-supplemented carbon and nitrogen sources respectively when 12% v/v of Escherichia coli ATCC 10536 suspension was inoculated. The harvested L-asparaginase has proceeded with a series of purification and the specific activity achieved after partial purification was 0.549 IU/mg. In conclusion, optimization of controlling parameters as well as supplementation of cooked chicken bone as substrate capable to further enhance the production of L-asparaginase.